THE EFFECT OF THE COVID-19 PANDEMIC ON THE PERFORMANCE AND STABILITY OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018 – 2021 (DIFFERENT TEST) - Pratama, Aldrin Yoga; Arifin, Lidiyawati (Bina Nusantara University, 2023)
The purpose of this study is to analyse the effect of the COVID-19 pandemic on the financial performance and stability of banking companies listed on the Indonesia Stock Exchange. The objects of research are banking companies listed on the Indonesia Stock Exchange in the period 2018 – 2021, which have experienced the impact of the pandemic, and publish their financial reports yearly. There are 46 sample data selected, through a purposive sampling technique with various criteria that have been determined, which are proxied by CAMELS analysis, according to Bank Indonesia regulations, and using secondary data as data tabulation. Model testing was carried out through the Wilcoxon Difference Test. The results showed that there was a significant difference in the average CAMELS value of 46 banking companies during the Covid-19 Pandemic, compared to before the pandemic. This finding implies many banking stakeholders in terms of maintaining their performance and enhancement of financial stability during negative shock events such as the COVID-19 pandemic.